A crise não reconhecida: identidade docente de professores do Ensino Fundamental II - Alfonsi, Selma Oliveira (2013)
This research aimed to investigate how the demands, which teachers notice that are made by the families and the school, affect their professional identity. 26 teachers, from a secondary private school in the city São Paulo, took part in this research. By using a questionnaire with open and closed questions, this research had the objective of identifying how the process of identity negotiation was carried out by these teachers and finding out if their identities are being affected by the attributions they notice are made, nowadays, by the school and families. The analyses were made according to the social conceptions of Dubar (2005 e 2009) concerning to the professional identity. For data analyses, it was also used the contributions of other authors who discuss identity and teachers professionalization, such as Placco e Souza (2010), Roldão (1998 e 2007), Marcelo (2009), Shulman (1986), Sacristán (1991), Nóvoa (2000) e Libâneo (2007). According to the data analyses it was possible to identify that the teachers are confused in relation to the roles they need to perform due to the multiple attributions they believe are demanded by the families and the school. Moreover, it was possible to notice that they are passing through a moment o crises, although they do not literally say they are in crises. In this study, crisis is considered as a rupture of what the individuals used to believe to be their roles, however, nowadays it seems that those roles are no longer fulfilling families and schools expectations